NOTES ON RAFFLESIA (RAFFLESIACEAE) IN SUMATRA WITH A NEW RECORD RAFFLESIA GADUTENSIS MEIJER - RIDHA MAHYUNI; YAYAN WAHYU C. KUSUMA; WIHERMANTO WIHERMANTO; J. F. VELDKAMP (Research Center for Biology, 2015)
MAHYUNI, R., KUSUMA,Y. W. C., WIHERMANTO & VELDKAMP, J. F. 2015. Notes on Rafflesia (Rafflesiaceae) in Sumatra with a new record Rafflesia gadutensis Meijer. Reinwardtia 14(2): 317 - 322. Pulau Mursala is a small island west of the Sibolga, Tapanuli Tengah District, North Sumatra, Indonesia. The occurrence of the genus Rafflesia (Rafflesiaceae) there has never been reported before. However, during a visit in April 2013 three populations are located close together with more than twenty buds and some rotting blooming flowers, Tetrastigma sp. was detected. Field observations could be made and material was collected for comparison with that in the Herbarium Bogoriense (BO). It was concluded that they are R.gadutensis Meijer, which is known from Padang, Ulu Gadut. Notes on its morphology are given. The distribution of species is discussed.